2020
DOI: 10.1371/journal.pone.0227209
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord separation time, predictors and healing complications in newborns with dry care

Abstract: The objective of this study was to explore the umbilical cord separation time, predictors, and healing complications from birth until the newborn was one month old. Design A quantitative longitudinal observational analytical study by stratified random sample was adopted. Setting Public health system hospitals in southern Spain and at newborns' homes. Participants Between April 2016 and December 2017, the study included 106 neonates born after 35-42 weeks of gestation whose umbilical cord was cured with water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…The umbilical cord, which consists of two arteries and one vein, connects the fetus with the placenta for blood circulation and has a significant influence on the development of the fetus [1][2][3]. The umbilical cord contains Wharton's jelly, which is a gelatinous substance composed of mucous polysaccharides that protects the blood vessels.…”
Section: Need For Studymentioning
confidence: 99%
See 3 more Smart Citations
“…The umbilical cord, which consists of two arteries and one vein, connects the fetus with the placenta for blood circulation and has a significant influence on the development of the fetus [1][2][3]. The umbilical cord contains Wharton's jelly, which is a gelatinous substance composed of mucous polysaccharides that protects the blood vessels.…”
Section: Need For Studymentioning
confidence: 99%
“…Studies have emphasized the importance of observing umbilical cord status through ultrasonography as part of prenatal care and during pregnancy [10], and have pointed out the practicality of using disinfectants or nursing methods for umbilical cord separation [11], but the importance of observing the thickness and status of the umbilical cord is still under-recognized in the clinical setting, to the point that the umbilical cord may not even be measured with a tape measure. The reason for this lack of awareness may be the inaccurate perception that the umbilical cord loses its function when separated from the mother after the neonate is born [3].…”
Section: Need For Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We applied Cox regression analysis considering to be dependent variable our primary outcome and as covariates the variables resulted significantly different ( p < 0.05) between the two study groups from univariate analysis and those suggested by the literature such as birth weight, Apgar score at 5 min, spring season (no or yes), type of delivery (vaginal delivery or cesarean section), and group assignment (PRE or POST) [ 8 , 9 ]. In addition, we performed a second Cox regression analysis considering to be covariates the variables resulted marginally different ( p < 0.2) between the two groups from univariate analysis (male sex and primiparity) and variables regarding parents’ status (primiparity, age of the mother, and difficulty of cord medication) that we hypothesize that could have influenced time of cord detachment.…”
Section: Methodsmentioning
confidence: 99%